Teacher's expectations about the teaching of care in mental health - Luciane Prado Kantorski; Leandro Barbosa de Pinho; Toyoko Saeki; Maria Conceição Bernardo de Mello e Souza (Universidade Federal de Goias, 2006)
Objective: The present study has for objective to detach the expectations of professors of psychiatric nursing on the education of the care in mental health. Methodology: The methodological boarding is qualitative and descriptive-analytical, in which the half-structuralized interviews had been used as instruments for the collection of data applied the 03 (three) professors, in 2001. Results: It was observed in the results that the professors emphasize the necessity of the humanization of the attendance in mental health, centered in a paradigm of the psychiatric reform. Conclusion: We concluded that the context of teaching-learning of mental health has been suffering influence of approaches as the psychoanalysis, the collective health and the relationship interpessoal.